Self-filling high-strength earth and rockfill dam water plugging material and preparation method thereof
Through the combination of bacteria-induced precipitation of calcium carbonate and water-soluble organic gel agent, the shortcomings of earth and rock dam water blocking materials in water resistance and strength are solved, and high strength and water resistance are improved, ensuring that the dam body is under water pressure impact stability and safety.
Patent Information
- Application Number
- CN202411291942.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing earth and rock dam water blocking materials cannot take into account both high strength and water resistance, resulting in unstable dam body under water pressure impact, affecting safety.
Bacteria-induced calcium carbonate precipitation MICP reaction is used to fill pores, and automatic drainage is achieved using the expansion force of water-soluble organic gel agent and bentonite, and combined with hydrophobic modified aggregates to enhance the water-reflective and mechanical properties of the dam body.
It significantly improves the water-reflective and mechanical properties of the dam body, enhances its resistance to ultra-high water pressure, and ensures the long-term use and safety of the dam body.
Smart Images

Figure CN119143435A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of plugging materials, and in particular relates to a preparation method of a self-filling high-strength earth-rock dam water-plugging material, and also relates to the self-filling high-strength earth-rock dam water-plugging material. Background Art
[0002] Earth-rock dam is a common water conservancy engineering structure, mainly used for water storage and flood control. It has the advantages of using local materials, saving construction materials and reducing long-distance transportation during dam construction. The structural design of earth-rock dam is simple, easy to repair, heighten and expand, and because the dam body of earth-rock dam is a loose granular structure of earth and rock, it has good performance in adapting to deformation. The mechanical properties of earth-rock dam materials have an important influence on the design and construction of earth-rock dams. Its mechanical properties requirements cover multiple aspects such as material strength, stability, and permeability, ensuring that earth-rock dams can remain stable and safe under various environmental conditions. Earth-rock dams are built by various methods. The raw materials used are mainly stone, soil or mixed materials. According to the selected raw materials, there is a certain gap between the granular materials of these two materials. When the reservoir is filled with water, due to the effect of water pressure, water penetrates through the gaps between earth and rock particles into the downstream dam body and the foundation of the dam foundation, resulting in certain leakage. At the same time, low strength will lead to the inability to resist the impact of water pressure, which will destroy the overall stability and affect the safety of actual use.
[0003] A Chinese patent (application number: 202310980931.1, publication number: CN117143448A, announcement date: 2023.12.01) discloses a method for preparing a water-blocking material for underground coal mine reinforcement, which uses a two-phase substance reaction to form an interpenetrating network structure to fill pores and achieve water blocking, but there are still pores in the interpenetrating network and physical filling alone cannot achieve effective drainage. Therefore, it is a difficult problem to be solved in the field of engineering materials to modify and improve the formula of the current traditional earth-rock dam water-blocking material and construct a green earth-rock dam water-blocking material that takes into account good anti-seepage performance and high strength. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a self-filling high-strength earth-rock dam water blocking material, so as to solve the problem that the earth-rock dam water blocking material in the prior art cannot have both high strength and water seepage resistance.
[0005] Another object of the present invention is to provide a self-filling high-strength earth-rock dam water blocking material.
[0006] The technical solution adopted by the present invention is a method for preparing a self-filling high-strength earth-rock dam water blocking material, which is specifically implemented according to the following steps:
[0007] Step 1, prefabricating active bacterial strain particles;
[0008] Step 2, adding the active bacteria particles obtained in step 1 and bentonite to soil and stone materials, mixing to obtain a premix, then adding a gelling agent, ball milling and mixing to obtain aggregate particles;
[0009] Step 3, placing the aggregate particles in step 2 on a mixer and stirring, and spraying an organic solution on the aggregate particles, i.e., performing hydrophobic modification to obtain modified aggregate;
[0010] Step 4, drying the modified aggregate obtained in step 3, and then mixing and stirring with urea to obtain a self-filling high-strength earth-rock dam water blocking material.
[0011] The present invention is also characterized in that:
[0012] In step 1, specifically:
[0013] Step 1.1, mixing peptone, sodium chloride, yeast extract and water, sterilizing at high temperature and high pressure to form a bacterial culture solution, culturing active bacteria with the bacterial culture solution to obtain a bacterial culture solution;
[0014] Step 1.2, dissolving agar powder in water, stirring, sterilizing, and drying under sterile conditions to obtain an agar plate; spreading the bacterial solution obtained in step 1.1 on the agar plate, sterilizing, drying and solidifying, and crushing into powder to obtain active bacterial granules.
[0015] In step 1.1, the active bacteria are any one of extracellular polymer-producing bacteria, urease-producing bacteria, denitrifying bacteria, sulfate-reducing bacteria, and methane-oxidizing bacteria.
[0016] In step 1.2, the dissolving temperature is 50-70°C, and the stirring time is 3-5h; during crushing, the rotation speed is 200-400r / min, and the crushing time is 3-5h.
[0017] In step 2, the mass ratio of active bacterial particles, bentonite and soil and stone is 1:1:3; the mass ratio of gelling agent to premix is 1:3-5.
[0018] In step 2, the bentonite is calcium-based bentonite or sodium-based bentonite; the gelling agent is any one of epoxy resin gelling agent, acrylic gelling agent, polyurethane gelling agent, and synthetic rubber gelling agent.
[0019] In step 3, the organic solution is prepared by mixing a coupling agent and water;
[0020] The coupling agent is any one of a sulfur silane coupling agent, an amino silane coupling agent, and an epoxy silane coupling agent; and the mass ratio of the organic solution to the aggregate particles is 5:1.
[0021] In step 4, the drying temperature is 100-150° C., the drying time is 2-4 hours, the stirring time is 3-5 hours, and the mass ratio of the modified aggregate to urea is 1:5-10.
[0022] Another technical solution adopted by the present invention is the earth-rock dam water-blocking material prepared by the preparation method of the self-filling high-strength earth-rock dam water-blocking material.
[0023] The beneficial effects of the present invention are as follows: the method of the present invention firstly utilizes the microorganisms of bacteria to induce the MICP reaction of calcium carbonate precipitation. Under the action of nutrients (urea), the urease of the bacteria themselves can decompose urea to form calcium carbonate precipitation, thereby filling the pores between the aggregates to improve their water-resistance performance, and reducing the porosity while improving the mechanical properties; utilizing a water-soluble organic gelling agent as the shell of the aggregate, when the whole material encounters water, the shell is dissolved by water, and the bentonite in the core body swells when encountering water, and with the help of the expansion force and the surface hydrophobic groups, the water inside the dam body is automatically discharged, and at the same time, the bacteria are dissolved in water and react with urea to generate calcium carbonate precipitation, and the drainage channel is filled, which is not only conducive to long-term use, but also after the drainage is completed, the calcium carbonate serves as a connection between the aggregates, effectively transmits the expansion force generated by the bentonite, and generates prestress, further improving the strength, and when subjected to ultra-high water pressure impact, the overall safety and stability of the dam body can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a structural diagram of the self-filling high-strength earth-rock dam water blocking material of the present invention.
[0025] In the figure, 1. active bacterial particles, 2. stone, 3. bentonite, 4. soil. DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] The preparation method of the self-filling high-strength earth-rock dam water blocking material of the present invention is specifically implemented according to the following steps:
[0028] Step 1: pre-prepare active bacterial strain particles; specifically:
[0029] Step 1.1, peptone, sodium chloride, yeast extract and water are mixed, and sterilized at high temperature and high pressure to form a bacterial culture solution, and active bacteria are cultured with the bacterial culture solution at a volume ratio of 1:100 to obtain a bacterial culture solution;
[0030] The culture time is 24h;
[0031] The active bacteria are any one of extracellular polymer-producing bacteria, urease-producing bacteria, denitrifying bacteria, sulfate-reducing bacteria, and methane-oxidizing bacteria;
[0032] The mass ratio of peptone to water is 1:100; the mass ratio of sodium chloride to water is 1:200; the mass ratio of yeast extract to water is 1:200;
[0033] Step 1.2, dissolving agar powder in water, stirring, sterilizing, and drying under sterile conditions to obtain an agar plate; spreading the bacterial solution obtained in step 1.1 on the agar plate, sterilizing, drying and solidifying, and crushing into powder to obtain active bacterial granules;
[0034] The dissolving temperature is 50-70°C and the stirring time is 3-5h;
[0035] During crushing, the speed is 200-400r / min and the crushing time is 3-5h;
[0036] The amount of bacterial solution inoculated on the agar plate is 100-300 μl;
[0037] Step 2, preparing aggregate particles: adding the active bacteria particles obtained in step 1 and bentonite to soil and stone materials, mixing at 30-40° C. for 2-4 hours to obtain a premix, then adding a gelling agent, ball milling and mixing to obtain aggregate particles;
[0038] The bentonite is specifically calcium-based bentonite or sodium-based bentonite;
[0039] The mass ratio of soil to stone in the soil-stone material is 1:1;
[0040] The mass ratio of active bacterial particles, bentonite and soil and stone is 1:1:3;
[0041] The mass ratio of gelling agent to premix is 1:3-5;
[0042] The gelling agent is any one of epoxy resin gelling agent, acrylic gelling agent, polyurethane gelling agent, and synthetic rubber gelling agent;
[0043] The ball milling mixing speed is 300-500r / min, and the ball milling mixing time is 3-5h;
[0044] Step 3, placing the aggregate particles in step 2 on a mixer and stirring, and spraying an organic solution on the aggregate particles, i.e., performing hydrophobic modification to obtain modified aggregate;
[0045] The organic solution is a mixture of a coupling agent and water; the concentration of the organic solvent is 0.5-1%;
[0046] The coupling agent is any one of a sulfur silane coupling agent, an amino silane coupling agent, and an epoxy silane coupling agent;
[0047] The mass ratio of organic solution to aggregate particles is 5:1;
[0048] The stirring speed is 200-400r / min, and the stirring time is 10-30min;
[0049] Step 4, drying the modified aggregate obtained in step 3, and then mixing and stirring with urea to obtain a self-filling high-strength earth-rock dam water blocking material;
[0050] The drying temperature is 100-150℃, the drying time is 2-4h; the stirring time is 3-5h;
[0051] The mass ratio of modified aggregate to urea is 1:5-10.
[0052] like Figure 1 As shown, it is a structural diagram of the self-filling high-strength earth-rock dam water blocking material prepared by the method of the present invention, wherein a single circle represents modified aggregate particles, and the modified aggregate particles are prepared from active bacteria particles 1, stone 2, bentonite 3 and soil 4 according to the steps.
[0053] The method of the present invention utilizes the microbial induced calcium carbonate precipitation MICP reaction of the urease of the bacteria and urea to form calcium carbonate precipitation, fills the pore structure in the traditional soil and stone materials, reduces the porosity and pore size, can improve the overall water seepage resistance of the dam body, and at the same time, the decrease in porosity makes the overall dam body more compact, and the ability to resist external water pressure is improved after the strength is improved; in addition, a water-soluble organic solvent is used as a shell to pre-wrap the bacteria and bentonite in the core, when encountering water that penetrates into the inside of the dam body, the outer shell is pre-dissolved in water to release the substance in the core, the bentonite swells when encountering water, and at the same time, due to the hydrophobic modification of the shell surface, the water inside the dam body is discharged by means of the expansion force and the surface hydrophobic groups; the bacteria dissolve and react with the urea dissolved in water to generate calcium carbonate precipitation, fill the position where the internal water is discharged, further densify, and at the same time, calcium carbonate is used as a connection between the aggregates to effectively transmit the expansion force generated by the bentonite, realize the generation of prestress in the whole, further improve the strength, and when subjected to ultra-high water pressure impact, the overall safety and stability of the dam body can be effectively improved.
[0054] Example 1
[0055] The preparation method of the self-filling high-strength earth-rock dam water blocking material of the present invention is specifically as follows:
[0056] Dissolve 5g of peptone, 2.5g of sodium chloride and 2.5g of yeast extract in 500ml of water to form a bacterial culture solution. After high temperature and high pressure sterilization, culture the extracellular polymer-producing bacteria and the bacterial culture solution at a ratio of 1:100 for 24 hours to obtain a bacterial culture solution. Add 10g of agar powder to 50℃, 500ml of water, stir and dissolve for 3 hours. After sterilization and drying under aseptic conditions, take 100 microliters of bacterial culture solution and spread it on it. After solidification, crush it at 200r / min for 3 hours to obtain active bacterial particles.
[0057] Traditional earth-rock dam materials were used, with the mass ratio of soil to stone being 1:1; the mass ratio of active bacterial particles, bentonite, and soil and stone being 1:1:3. The mixture was mixed at 30°C for 2 hours, and then the premix was added to the epoxy resin gelling agent, with the mass ratio of gelling agent to premix being 1:3. The mixture was ball-milled at 300 r / min for 3 hours.
[0058] The sulfur silane coupling agent was prepared into a 0.5% aqueous solution, the above aggregate particles were placed on a mixer, the ratio of the aqueous solution to the aggregate particles was adjusted to 5:1, the rotation speed was 200 r / min, the silane solution was sprayed on the aggregate particles and stirred for 10 minutes.
[0059] The modified aggregate obtained above was dried at 100°C for 2 hours, and fully mixed with urea at room temperature for 3 hours. The urea content was 5 times that of the active bacterial culture solution. It was then filled in the actual application to form a dam body according to the traditional compaction method.
[0060] Example 2
[0061] The preparation method of the self-filling high-strength earth-rock dam water blocking material of the present invention is specifically as follows:
[0062] Dissolve 5g of peptone, 2.5g of sodium chloride, and 2.5g of yeast extract in 500ml of water to form a bacterial culture solution. After high temperature and high pressure sterilization, culture the extracellular polymer-producing bacteria with the bacterial culture solution at a ratio of 1:100 for 24 hours to obtain a bacterial culture solution. Add 10g of agar powder to 500ml of water at 60℃ and stir to dissolve for 3.5 hours. After sterilization and drying under aseptic conditions, take 150 microliters of bacterial culture solution and lay it on it. After solidification, crush it at 250r / min for 3.5 hours to obtain active bacterial particles.
[0063] Traditional earth-rock dam materials are used, in which the ratio of soil to stone is 1:1; the ratio of active bacteria particles, bentonite, soil and stone is 1:1:3, and they are mixed under dry conditions at a temperature of 30°C for 2.5 hours. The premix is then added to the epoxy resin gelling agent with a mass ratio of gelling agent to premix of 1:3, and ball milled at 350r / min for 3.5 hours.
[0064] The sulfur silane coupling agent is prepared into a 0.6% aqueous solution. The above aggregate particles are placed on a mixer, the ratio of the aqueous solution to the aggregate particles is adjusted to 5:1, the rotation speed is 250r / min, and the aggregate particles are sprayed with the silane solution and stirred for 15 minutes.
[0065] The modified aggregate obtained above was dried at 110°C for 2.5 hours and fully mixed with urea at room temperature for 3.5 hours. The urea content was 6 times that of the active bacterial culture solution. It was then filled in the actual application situation according to the traditional compaction method to form a dam body.
[0066] Example 3
[0067] The preparation method of the self-filling high-strength earth-rock dam water blocking material of the present invention is specifically as follows:
[0068] Dissolve 5g of peptone, 2.5g of sodium chloride, and 2.5g of yeast extract in 500ml of water to form a bacterial culture solution. After high temperature and high pressure sterilization, culture the urease-producing bacteria and the bacterial culture solution at a ratio of 1:100 for 24 hours to obtain a bacterial culture solution. Add 10g of agar powder to 500ml of water at 65℃ and stir to dissolve for 4 hours. After sterilization and drying under aseptic conditions, take 200 microliters of bacterial culture solution and lay it on it. After solidification, crush it at 300r / min for 4 hours to obtain active bacterial particles.
[0069] Traditional earth-rock dam materials are used, in which the ratio of soil to stone is 1:1; the ratio of active bacteria particles, bentonite, soil and stone is 1:1:3, and they are mixed under dry conditions at 35°C for 3 hours. The premix is then added to the acrylic gelling agent with a mass ratio of gelling agent to premix of 1:4, and the mixture is ball-milled at 400r / min for 4 hours.
[0070] The sulfur silane coupling agent is prepared into a 0.75% aqueous solution. The above aggregate particles are placed on a mixer, the ratio of the aqueous solution to the aggregate particles is adjusted to 5:1, the rotation speed is 300 r / min, and the aggregate particles are sprayed with the silane solution and stirred for 20 minutes.
[0071] The modified aggregate obtained above was dried at 130°C for 3 hours, and fully mixed with urea at room temperature for 4 hours. The urea content was 8 times that of the active bacterial culture solution. It was then filled in the actual application situation according to the traditional compaction method to form a dam body.
[0072] Example 4
[0073] The preparation method of the self-filling high-strength earth-rock dam water blocking material of the present invention is specifically as follows:
[0074] Dissolve 5g of peptone, 2.5g of sodium chloride, and 2.5g of yeast extract in 500ml of water to form a bacterial culture solution. After high temperature and high pressure sterilization, culture the urease-producing bacteria and the bacterial culture solution at a ratio of 1:100 for 24 hours to obtain a bacterial culture solution. Add 10g of agar powder to 500ml of water at 70℃ and stir to dissolve for 5 hours. After sterilization and drying under aseptic conditions, take 300 microliters of bacterial culture solution and lay it on it. After solidification, crush it at 400r / min for 5 hours to obtain active bacterial particles.
[0075] Traditional earth-rock dam materials were used, in which the ratio of soil to stone was 1:1; the ratio of active bacteria particles, bentonite, and soil and stone was 1:1:3. They were mixed at a temperature of 40°C for 4 hours, and then the premix was added to the acrylic gelling agent with a mass ratio of gelling agent to premix of 1:5. The mixture was ball-milled and mixed at 500r / min for 5 hours.
[0076] The sulfur silane coupling agent is prepared into a 1% aqueous solution. The above aggregate particles are placed on a mixer, the ratio of the aqueous solution to the aggregate particles is adjusted to 5:1, the rotation speed is 400r / min, and the aggregate particles are sprayed with the silane solution and stirred for 30 minutes.
[0077] The modified aggregate obtained above was dried at 150°C for 4 hours, and fully mixed with urea at room temperature for 5 hours. The urea content was 10 times that of the active bacterial culture solution. It was then filled in the actual application to form a dam body according to the traditional compaction method.
[0078] Table 1 is a comparison of the anti-seepage performance and compaction degree of the earth-rock dams of Examples 1 to 4 and the traditional earth-rock dams
[0079]
[0080] As can be seen from Table 1, the present invention utilizes the expansion properties of bentonite to pre-form a certain prestress inside the dam body to resist the impact of external water pressure, and at the same time utilizes the MICP reaction of specific bacteria to generate calcium carbonate precipitation to fill the pores. After the compaction degree is improved, the anti-seepage performance and strength of the dam body are further improved, thereby enhancing the safety and stability of the dam body.
Claims
1. A method for preparing a self-filling high-strength earth-rock dam water blocking material, characterized in that: Follow the steps below to implement it: Step 1, prefabricating active bacterial strain particles; Step 2, adding the active bacteria particles obtained in step 1 and bentonite to soil and stone materials, mixing to obtain a premix, then adding a gelling agent, ball milling and mixing to obtain aggregate particles; Step 3, placing the aggregate particles in step 2 on a mixer and stirring, and spraying an organic solution on the aggregate particles, i.e., performing hydrophobic modification to obtain modified aggregate; Step 4, drying the modified aggregate obtained in step 3, and then mixing and stirring with urea to obtain a self-filling high-strength earth-rock dam water blocking material.
2. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 1, characterized in that: In the step 1, specifically: Step 1.1, mixing peptone, sodium chloride, yeast extract and water, sterilizing at high temperature and high pressure to form a bacterial culture solution, culturing active bacteria with the bacterial culture solution to obtain a bacterial culture solution; Step 1.2, dissolving agar powder in water, stirring, sterilizing, and drying under sterile conditions to obtain an agar plate; spreading the bacterial solution obtained in step 1.1 on the agar plate, sterilizing, drying and solidifying, and crushing into powder to obtain active bacterial granules.
3. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 2, characterized in that: In the step 1.1, the active bacteria are any one of extracellular polymer-producing bacteria, urease-producing bacteria, denitrifying bacteria, sulfate-reducing bacteria, and methane-oxidizing bacteria.
4. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 2, characterized in that: In the step 1.2, the dissolving temperature is 50-70° C., and the stirring time is 3-5 h; during crushing, the rotation speed is 200-400 r / min, and the crushing time is 3-5 h.
5. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 1, characterized in that: In the step 2, the mass ratio of active bacterial particles, bentonite and soil and stone is 1:1:3; the mass ratio of gelling agent to premix is 1:3-5.
6. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 1, characterized in that: In the step 2, the bentonite is calcium-based bentonite or sodium-based bentonite; the gelling agent is any one of epoxy resin gelling agent, acrylic gelling agent, polyurethane gelling agent, and synthetic rubber gelling agent.
7. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 1, characterized in that: In step 3, the organic solution is formed by mixing a coupling agent and water; the coupling agent is any one of a sulfur silane coupling agent, an amino silane coupling agent, and an epoxy silane coupling agent; and the mass ratio of the organic solution to the aggregate particles is 5:
1.
8. The method for preparing the self-filling high-strength earth-rock dam water blocking material according to claim 1, characterized in that: In step 4, the drying temperature is 100-150° C., the drying time is 2-4 hours, the stirring time is 3-5 hours, and the mass ratio of the modified aggregate to urea is 1:5-10.
9. The earth-rock dam water-blocking material prepared by the method for preparing the self-filling high-strength earth-rock dam water-blocking material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of concrete self-repairing microcapsule
CN115073055A
Vertical barrier based on microbial mineralization and preparation method thereof
CN115583818A
Regenerated coarse aggregate modification method based on urease mineralization deposition
CN117125915A
Strengthening method for recycled aggregate using biological deposition
WO2022253355A1
Cited By
Earthen ruins reinforcing mortar material based on hydraulic lime and MICP technology and preparation method and application thereof
CN119638350A
